2021
DOI: 10.1038/s41467-021-21573-x
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis-targeting chimera against BCL-XL destroys tumor-infiltrating regulatory T cells

Abstract: Regulatory T cells (Tregs) play an important role in maintaining immune homeostasis and, within tumors, their upregulation is common and promotes an immunosuppressive microenvironment. Therapeutic strategies that can eliminate Tregs in the tumor (i.e., therapies that do not run the risk of affecting normal tissues), are urgently needed for the development of cancer immunotherapies. Here we report our discovery of B-cell lymphoma extra-large (BCL-XL) as a potential molecular target of tumor-infiltrating (TI) Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 39 publications
(32 reference statements)
0
31
0
Order By: Relevance
“…DT2216 has demonstrated preclinical activity against BCL-X L -dependent T cell lymphomas without causing significant platelet toxicity specifically degrading BCL-X L while sparing BCL-2 [ 47 , 49 ]. An additional similar PROTAC, PZ15227, has also recently emerged which induces BCL-X L polyubiquitination and degradation [ 50 ]. BCL-X L has been reported to be highly expressed in the tumor-infiltrating regulatory T-cells (Treg) population in several cancers.…”
Section: Therapeutic Strategies For Promoting Apoptosis Directly—intrinsic Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…DT2216 has demonstrated preclinical activity against BCL-X L -dependent T cell lymphomas without causing significant platelet toxicity specifically degrading BCL-X L while sparing BCL-2 [ 47 , 49 ]. An additional similar PROTAC, PZ15227, has also recently emerged which induces BCL-X L polyubiquitination and degradation [ 50 ]. BCL-X L has been reported to be highly expressed in the tumor-infiltrating regulatory T-cells (Treg) population in several cancers.…”
Section: Therapeutic Strategies For Promoting Apoptosis Directly—intrinsic Pathwaymentioning
confidence: 99%
“…BCL-X L has been reported to be highly expressed in the tumor-infiltrating regulatory T-cells (Treg) population in several cancers. Both PROTAC compounds have demonstrated induction of apoptosis in Tregs and the activation of tumor infiltrating CD8+ T cells resulting in a decrease in tumor growth in immunocompetent tumor models; this suggests that targeting of BCL-X L may also have the potential to improve cancer immunotherapy [ 50 ]. UBX1325 (Unity Biotechnology, San Franscisco, CA, USA), another specific BCL- X L inhibitor, is also being evaluated in patients with diabetic macular edema widening the scope of this class of agents beyond cancer (NCT04537884, NCT04857996).…”
Section: Therapeutic Strategies For Promoting Apoptosis Directly—intrinsic Pathwaymentioning
confidence: 99%
“…Since on-target thrombocytopenia is a major hurdle in the clinical development of BCL-X L inhibitors, we recently adopted a novel PROTAC technology to overcome this toxicity by converting ABT263 (BCL-X L /2 dual inhibitor) into a BCL-X L selective PROTAC, named DT2216 (20)(21)(22). DT2216 is currently in phase I clinical studies for patients with relapsed/refractory malignancies (NCT04886622).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, using emerging Proteolysis Targeting Chimera (PROTAC) technology, we successfully converted ABT263 (a BCL-X L /2 inhibitor) into DT2216, a plateletsparing BCL-X L -selective PROTAC that targets BCL-X L to the Von Hippel-Lindau (VHL) E3 ligase for ubiquitination and proteasomal degradation (20). DT2216 has shown promising antitumor activities in BCL-X L -dependent hematologic malignancies when used as single agent therapy and in multiple solid tumors when combined with conventional chemotherapy (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that tumor immune cells can perform vastly different or even opposite functions under the influence of the tumor microenvironment ( Jiménez-Sánchez et al, 2017 ; Wagner et al, 2019 ; Luoma et al, 2020 ; Kolb et al, 2021 ), with some studies suggesting that m6A modification plays an important regulatory role in these immune cells. Here, we discuss the relationship between immune cell infiltration and m6A modification in HNSCC, with a view to providing directions for future studies.…”
Section: Relationship Between M6a and Immune Cells In The Tumor Microenvironmentmentioning
confidence: 99%